Too strong? Barriers from getting support before a suicide attempt in Lithuania. Issue 8 (13th September 2016) - Dadašev, Said; Skruibis, Paulius; Gailienė, Danutė; Latakienė, Jolanta; Grižas, Antanas
ABSTRACT: The study aimed to understand the tendencies of help seeking before a suicide attempt in Lithuania. An analysis of interviews with 21 Lithuanian adults demonstrated strong avoidance of seeking help. The main reasons for avoidance included a lack of trust in other people, thinking that one must solve problems independently without sharing them, avoiding troubling others, and a belief that showing genuine emotions is a sign of weakness. These findings may contribute to suicide prevention by more deeply understanding the barriers to help seeking among high suicide risk groups, particularly in countries with a traumatic historical experience.